The Impact of Smartphone Usage on Academic Performance Among Students at King Abdulaziz University, Saudi Arabia: A Subgroup Analysis Based on Year of Study and Field of Specialization - Almakky, Hana Ghazy (Journal of Ecohumanism, 2025)
The rapid development of smartphones has made them an inseparable part of education for university students, using such devices to communicate, learn, and access information. However, together with a lot of advantages, smartphones might turn into a source of serious disruptions, and their widespread use—especially in class—raises questions regarding the impacts on the academic progress of students. This research looks at the impact of smartphone addiction on the academic achievement of students at King Abdulaziz University in Saudi Arabia. To thoroughly examine if there is the differential impact of SA across the students, the academic year and the field of study were administered. Data of 103 students who completed this online survey were collected on addiction behavior, classroom usage, and academic achievement. The findings indicate that even patterns of use that are very addictive, like compulsive and only in the classroom, negatively affect advancement only to a tiny degree. However, academic maturity plays a huge role in how smartphones act as a divertive device. Indeed, senior students displayed self-regulated behavior and concentrated more on their academics than younger students, presumably by virtue of better time management skills honed during their longer study tenure. Addictive behaviors intercorrelate to indicate a cluster of dependent behaviors, while academic outcomes have not suffered significantly. Moreover, no significant variations in the impact of smartphone addiction on academic progress were observed among disciplines, which thus shows consistency in the effects across different fields of study. Such findings emphasize the complicated role of smartphone addiction in educational settings. While smartphone use is prevalent, its impact on learning outcomes depends on students’ maturity and abilities to regulate their behavior. It recommends that universities should develop polices in computer usage and self-regulation specifically for young people around smart phone usage that would assist in enhancing students learning outcomes.